2014
DOI: 10.1111/aab.12148
|View full text |Cite
|
Sign up to set email alerts
|

Post‐infectional dynamics of leaf spot disease in Withania somnifera

Abstract: Withania somnifera is a high value medicinal plant, native to Indian sub-continent, and is extensively used in traditional systems of medicine. It is highly prone to leaf spot disease caused by Alternaria alternata, that may affect the quality of crude herbal drugs. In the present study, the accumulation of ROS (reactive oxygen species) was detected histochemically within the infected host tissue, using H 2 DCFDA (2 ′ ,7 ′ -difluorodihydrofluorescein diacetate) and DAB (3,3 ′ -diaminobenzidine) staining method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…For H 2 DCFDA assay, pieces of second leaf were incubated in 10 μM H 2 DCFDA and were vacuum infiltered for 5 min. The leaves were then washed with double distilled water and were observed under the confocal microscope using laser beam of excitation 488 nm [ 33 , 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…For H 2 DCFDA assay, pieces of second leaf were incubated in 10 μM H 2 DCFDA and were vacuum infiltered for 5 min. The leaves were then washed with double distilled water and were observed under the confocal microscope using laser beam of excitation 488 nm [ 33 , 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…Further, a hyphal structure along with an increase in crystal-like substances near the aperture of stomata was also observed in diseased leaves. Similarly, post inflectional dynamics of leaf spot pathogen in W. somnifera was studied to higher level by Sharma et al (2014). Microscopic assessment using confocal microscopy of infected leaves showed the emergence of conidiophores through stomata while SEM pointed out stomata to be the site for fungal access into the host.…”
Section: Ultrastructural Changes Associated In Plants Affected By Dismentioning
confidence: 99%
“…At the gene expression level, Tuffen (2010) reported symptoms of significantly reduced leaf size, chlorosis and increased branching along with the decrease in the expression of photosynthesis related genes in phytoplasma infected C. roseus . Sharma et al (2014) showed that leaf spot disease had significant effect on the photosynthetic efficiency of Withania , as continuous decline in carboxylation rate was observed with the progression of the disease. At the level of metabolite changes associated with pathogen infection, Choi et al (2004) observed that Phytoplasma-infected C. roseus plants showed a noticeable lightening of older leaves, which was associated with the accumulation of carbohydrates in the source leaves (Lepka et al , 1999).…”
Section: Effect Of Disease On Photosynthetic Machinerymentioning
confidence: 99%
“…According to World Health Organization (WHO), the international market of herbal products is around $6.2 billion, which is poised to grow to $5 trillion by the year 2050. Among the herbal plants, Ashwagandha (Withania somnifera (L.) Dunal) is an important medicinal plant widely used in various traditional systems of medicines like Ayurveda, Sidha, Unani, Homeopathy and others (Mir et al, 2012;Sharma et al, 2014). Ashwagandha is an erect, evergreen, perennial shrub belongs to the family Solanaceace.…”
Section: Introductionmentioning
confidence: 99%